SOSIALISASI PEMBUATAN DETERJEN CAIR DI LINGKUNGAN ANGGOTA KOPERASI SUMBER REZEKI KOTA BINJAI - Lestari, Pratiwi Putri; Wijayanna, Surya Sevi; Rahmayana, Rahmayana; Zainal, Zainal; Sukmawati, Sukmawati; Rizky, Putri; Simanjuntak, Dedi Sofyan; Fadillah, Eva; Bahri, Tasya; Fahlevi, Tya (Universitas Islam Sumatear Utara, 2024)
Empowering housewives as members of society and still being classified as productive workers is very important, aimed at increasing awareness and independence in business, as well as expanding employment opportunities to increase family income in an effort to achieve a happy and prosperous family. In this regard, this can be done through various alternative activities, including training in making liquid detergent. Soap is a commodity that cannot be separated from household needs. It can be said that part of the routine expenses for housewives each month is allocated to purchasing washing soap. The methods used in this community service activity are socialization, discussion and practice or demonstration regarding raw materials, work procedures and calculation of production costs for making liquid detergent. The training participants are members of the Sumber Rezeki Cooperative in Sumber Mulyo Rejo Village with a total of 20 training participants. This activity was carried out in Sumber Mulyo Rejo Village, Binjai City on February 24 2024. The evaluation plan for service activities is that the target number of training participants is achieved, the training objectives are achieved well, the planned material targets are achieved and the participants are able to understand the training material. The result of this training activity in making liquid detergent is that members of the Sumber Rezeki cooperative in Binjai city have knowledge of making liquid detergent and provide innovation to improve the economy.